The impact of hepatitis B surface antigen on natural killer cells in patients with chronic hepatitis B virus infection. (3rd May 2021) - Du, Yanqin; Anastasiou, Olympia E.; Strunz, Benedikt; Scheuten, Janina; Bremer, Birgit; Kraft, Anke; Kleinsimglinhaus, Karolina; Todt, Daniel; Broering, Ruth; Hardtke‐Wolenski, Matthias; Wu, Jun; Yang, Dongliang; et al.
Abstract: Background & Aims: During chronic hepatitis B virus (HBV) infection, suppressed functionality of natural killer (NK) cells might contribute to HBV persistence but the underlying mechanisms remain elusive. A peculiar feature of HBV is the secretion of large amount of hepatitis B surface antigen (HBsAg). However, the effect of HBsAg quantities on NK cells is unclear. The aim was to determine the effects of HBsAg quantities on NK cell functionality in patients with chronic hepatitis B (CHB). Methods: Eighty CHB patients were included and categorized into four groups based on their HBsAg levels. As a control, 30 healthy donors were enrolled. NK cell frequency, phenotype and function were assessed using flow cytometry and correlated with HBsAg levels and liver enzymes. Results: Compared to the healthy controls, a reshaping of NK cell pool towards more CD56 bright NK cells was observed during CHB infection. Importantly, NK cells in patients with low HBsAg levels (<100 IU/mL) displayed an activated phenotype with increased expression of activation makers CD38, granzyme B and proliferation marker Ki‐67 while presenting with defective functional responses (MIP‐1β, CD107a) at the same time. Furthermore, NK cell activation was negatively correlated with patient HBsAg levels while NK function correlated with patient age. Conclusions: The differential regulation of NK cell phenotype and function suggests that activation of NK cells in patients with low serum HBsAg levels may contribute to HBV clearance.